Spatial Analysis of a Tuberculosis Incidence in Magelang City in 2021 - Amira Nada Fatikha; Martini Martini; Retno Hestiningsih; Nissa Kusariana (Disease Prevention and Public Health Journal, 2021)
Background: TubercuIosis is a health problem of global concern, especially in Southeast Asia. Indonesia is the second-Largest contributor to tuberculosis after India. Some causes influence the increasing burden of tuberculosis in Indonesia, including environmental and socio-economic factors. Therefore, spatial analysis is needed to see the distribution of tuberculosis cases based on risk factors. This study focuses on conducting spatial analysis in Magelang City. Methods: This research is a quantitative descriptive observational study using an ecologic study approach. The sample size in this study was 38 tuberculosis patients with total sampling. Data collection was carried out using observation sheets. Data analyzed by software ArcGIS. results: The spatial pattern of distribution occurred according to the Iow population density (97.4%), the environmental temperature meet the requirements (84.2%), the air humidity meet the requirements (100%), the BCG immunization coverage was not being met (100%), the distance to health services is close (100%), the household with low-level social welfare is at the most (23.7%). Conclusion: An urban village with the highest tuberculosis cases is in the household with low-level social welfare is at the most. There is a need to improve social welfare and coverage of BCG immunization.